Mapping of Forest and Land Fire Vulnerability Levels in Kabupaten Tanah Laut, Provinsi Kalimantan Selatan - Marbun, Yessyca Dian Patriani; Kumalawati, Rosalina; Iskandar, Akhmad; Efendi, Muhammad (Universitas Lambung Mangkurat, 2024)
The purpose of this study is to determine the level of vulnerability to forest and land fires in Tanah Laut Regency and to provide input recommendations for preventing forest and land fires related to the high areas prone to forest and land fires in Tanah Laut Regency. This study uses a mix method or quantitative and qualitative methods. The quantitative method is a spatial approach used for mapping the vulnerability to forest and land fires, while qualitative methods with descriptive analysis are used to provide input recommendations for preventing forest and land fires in Tanah Laut Regency. The results of this study are that the highest level of vulnerability to forest and land fires is at the High level with an area of 217,211.08 hectares or 56.51% of the total area of Tanah Laut Regency. Input recommendations for preventing forest and land fires are carried out by involving various steps, one of which is conducting a depth interview with the Manggala Agni service and the sub-district head in Tanah Laut Regency regarding the Patrol SOP carried out to prevent forest and land fires.